Atlas Optical Coherence Tomography of Macular Diseases and Glaucoma - Gupta, Vishali; Amod Gupta; Mangat Ram Dogra (Panamá : Jaypee-Highlights, 2012)
The fourth edition of this atlas has been completely updated to provide the latest thinking and technology developments in the use of OCT with macular diseases and glaucoma. Beginning with an introduction to OCT, the following section discusses its use with a range of conditions and disorders associated with macular diseases such as macular hole, foveal haemorrhage and retinal trauma. The final section examines the use of OCT for diagnosis and management of glaucoma.
CTION 1: INTRODUCTION TO OCT 1. Basics of Optical Coherence Tomography 2. OCT Equipment 3. Technique of Acquiring OCT 4. Selection of Scan Protocols 5. Interpretation of OCT Scan SECTION 2: OCT PATTERNS IN VARIOUS MACULAR DISEASES 6. Diabetic Macular Edema 7. Idiopathic Central Serous Chorioretinopathy (ICSC) 8. Macular Hole 9. Retinal Vascular Occlusions 10. Retinal Vasculitis 11. Epiretinal Membranes 12. Age-Related Macular Degeneration 13. OCT in Choroidal Neovascular Membranes 14. Juxtafoveal Telangiectasia 15. Heredodystrophic Disorders 16. Foveal Hemorrhage 17. Photic Maculopathy 18. Optic Disc Pits 19. Inflammatory Diseases of Retina-choroid 20. Retinal Angiomatosis Proliferation 21. Retinal Trauma 22. Macular Evaluation following Retinal Detachment Surgery 23. Degenerative Myopia 24. Postoperative Endophthalmitis SECTION 3: GLAUCOMA 25. Introduction 26. OCT in Glaucoma 27. OCT Scans for Glaucoma 28. Stratus OCT in Glaucoma 29. Case Illustrations 30. Limitations of OCT 31. The Spectral Domain OCT for Glaucoma
Incluye índice de temas
InIdioma en inglés
Keywords: GLAUCOMA; OFTALMOLOGÍA